Psychosocial Experiences of Buddhist Students in a Muslim-Majority Student Environment - Maritza; Syahidah; Purnomo (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study explored the psychosocial experiences of Buddhist students as a religious minority within a Muslim-majority school environment at SMP Negeri 4 Salatiga. Using an interpretive phenomenological approach informed by Freudian psychoanalytic theory, particularly the concept of ego defense mechanisms, the research examined two participants (S1 and S2) through in-depth semi-structured interviews and supporting observation. Data were analyzed following the Colaizzi method, involving repeated reading of transcripts, extraction of significant statements, formulation of meanings, thematic clustering, and construction of an exhaustive description of the participants’ lived experience. Six interrelated themes emerged: acceptance of religious identity, peer social relations, school support and cultural sensitivity, structural barriers to religious practice, ego defense mechanisms, and the meanings constructed from being a minority student. Findings showed that although both participants generally adapted well and experienced supportive peer relationships, they also encountered subtle challenges such as microaggressions from teachers and limited facilities for worship. Participants employed mechanisms such as rationalization, suppression, sublimation, and identification to maintain psychological stability. The study concludes that psychosocial wellbeing among minority students depends not only on formal inclusive policies but also on the consistency of everyday interactions, underscoring the need for stronger multicultural competence among teachers and school counselors.